Developmental state dan tantangan globalisasi: Pengalaman Korea Selatan - Winanti, Poppy Sulistyaning (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2003)
This article aims to examine the impact of globalization to developmental state model as practiced in South Korean. The model, which requires a high state intervention in economic development process, in a great tension with spririt of democratization and economic liberalization or minimal state intervention embedded in globalization. Contrary to commonly assumed, this article argues that the developmental state to retain states critical role in economic development, yet it shall improve its transparency dan democratic policy-making.